Tolerance induction by hair-specific keratins in murine alopecia areata - Erb, Ulrike; Freyschmidt-Paul, Pia; Zöller, Margot (Journal of leukocyte biology, 2013)
Two hair-specific keratins were identified as murine alopecia areata autoantigens; application of peptides from these keratins in a non-immunogenic form serves well as therapeutics.
Gesehen am 12.02.2021